Tolling by breeding Brent and small Canada Geese - Boyd, H (Wildfowl, 1999)
On 7 July 1989, three pairs of small Canada Geese Branta canadensis hutchinsii nesting on adjacent islets in a lake on Prince Charles Island (67.47 N, 76.12 W), in Foxe Basin, NWT, approached and moved after me as I waded out to inspect their nests. On 30 June 1991, about thirty Brent Geese Branta bernicla nigricans nesting on Rainy Island (67.44 N, 102.30 W), a the mouth of the Perry River, NWT, formed into a tight group on the water, approached me closely and followed me for several minutes as I walked along the shore. Small Canada Geese and Lesser Snow Geese Anser c. caerulescens that were also nesting on the island did not.